Application of path modelling to identify causal relationships of in vitro production of sesquiterpenes in Gyrinops walla Gaetner - Sachithri Munasinghe; S Somaratne; S.R. Weerakoon; C. Ranasinghe (Lembaga Sembilan Tiga Community, 2022)
The recent recovery of Gyrinops walla as a potential producer of market-quality agarwood in mature damaged woods and branches, the intense illicit felling and exportation walla leading to the verge of extinction from Sri Lankan flora. The sustainable utilization of G. walla undoubtedly enhances the foreign exchange of the country by tissue culture-based techniques for the sustainable exploitation and conservation of the vulnerable G. walla species. Partial Least Square Structural Equation Model (PLS-SEM) was developed to elucidate the causal relationships between the latent variables; the cultured materials (CULTM), type of elicitation (ELI), concentration/intensities of the elicitors (CON), time of incubation (INCB) with the occurrence of sesquiterpenes (SES). The path coefficients of the PLS-SEM model showed direct effects of CULTM -> SES (β = -0.509, t = 6.468, p < 0.05) (hypothesis - H3), INCB -> SES (β = 0.421, t = 5.037, p < 0.05) (hypothesis - H1) and ELI + CON -> SES (β = -0.282, t = 5.792, p < 0.05) (hypothesis-H6) on induction of the production of sesquiterpenes. The PLS-SEM model developed the study proved the applicability in exploring the causal relationships between the deterministic factors that effect on artificial elicitation in the production of sesquiterpenes.